The Development of Small and Medium Entreprises Clusters in Indonesia - Tambunan, Tulus; Supratikno, Hendrawan (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
Small and Medium Enterprises (SMEs) in Indonesia are very important not only for employment creation, but also as important sources of economic growth and foreign currencies generation through exports. Since the early 1980s, the Indonesian government has adopted SME development policy through a clustering approach. This paper reviews the existing empirical studies on development of SME clusters in Indonesia. This paper deals with two main questions. First, what are the critical success factors of development of an SME cluster. Second to what extent this policy has contributed to the dynamic of SME clusters in the country. The paper argues that in many cases, the development policy has not been so successful. In essence, most failures can be attributed to the fact that one or more critical factors for successful SME cluster development were either not existing or not addressed correctly. Neglecting cluster linkage to markets is one reason of the failure. Prerequisite for successful cluster development is the clusters potential to access to growing market, either domestic or abroad.